2004
DOI: 10.1002/masy.200451102
|View full text |Cite
|
Sign up to set email alerts
|

Aluminate and Magnesiate Complexes as Propagating Species in the Anionic Polymerization of Styrene and Dienes

Abstract: The influence of MgR2 and AlR3 additives on alkyllithium initiators in the anionic polymerization of butadiene has been investigated in non polar solvents. A strong decrease of the diene polymerization rate in the presence of the two Lewis acids was observed, similarly to that observed in the retarded anionic polymerisation of styrene. With n,s‐Bu2Mg, the percentage of 1,2 vinyl units increases with the [Mg]/[Li] ratio. This behavior is specific to magnesium derivatives bearing secondary alkyl groups and likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The K atoms bridge between two TMP units, forming strong K-N contacts [K1-N1, 3.052(2); K1-N2, 3.053(2) Å], with a bridging N1-K1-N2 angle of 146.72 (6) . Mg occupies a distorted trigonal planar site [N1-Mg1-N2 00 , 133.63(9); N1-Mg1-C20, 115.57 (14); N2 00 -Mg1-C20, 110.28 (14)], and the inner n-butyl appendages point alternately above and below the ring plane, in a similar fashion to that observed in the tetrameric polymorph 4. Interestingly, continuing the preinverse-crown notion (i.e., 5 contains basic, reactive n-butyl ligands which are capable of inducing arene deprotonation), hexameric 5 appears to represent the perfect template to produce the arene-ide inverse crowns 2a and 2b, as it is directly comparable in terms of aggregation state and conformation with all its n-butyl appendages still intact to deprotonate benzene or toluene.…”
Section: Synthesis and Characterisation Of Potassium Pre-inversecrownsmentioning
confidence: 84%
See 3 more Smart Citations
“…The K atoms bridge between two TMP units, forming strong K-N contacts [K1-N1, 3.052(2); K1-N2, 3.053(2) Å], with a bridging N1-K1-N2 angle of 146.72 (6) . Mg occupies a distorted trigonal planar site [N1-Mg1-N2 00 , 133.63(9); N1-Mg1-C20, 115.57 (14); N2 00 -Mg1-C20, 110.28 (14)], and the inner n-butyl appendages point alternately above and below the ring plane, in a similar fashion to that observed in the tetrameric polymorph 4. Interestingly, continuing the preinverse-crown notion (i.e., 5 contains basic, reactive n-butyl ligands which are capable of inducing arene deprotonation), hexameric 5 appears to represent the perfect template to produce the arene-ide inverse crowns 2a and 2b, as it is directly comparable in terms of aggregation state and conformation with all its n-butyl appendages still intact to deprotonate benzene or toluene.…”
Section: Synthesis and Characterisation Of Potassium Pre-inversecrownsmentioning
confidence: 84%
“…Hexamer 5 features a 24-atom (KNMgN) 6 centrosymmetric ring, with two and three coordinate K and Mg centres respectively, although the K is positioned in relatively close proximity to one of the a-carbon atoms of the neighbouring n-butyl groups [K1-C20, 3.143(5); K1-C20 0 , 3.243(5)Å]. Mg occupies a distorted trigonal planar site [N1-Mg1-N2 00 , 133.63(9); N1-Mg1-C20, 115.57 (14); N2 00 -Mg1-C20, 110.28 (14)], and the inner n-butyl appendages point alternately above and below the ring plane, in a similar fashion to that observed in the tetrameric polymorph 4. Mg occupies a distorted trigonal planar site [N1-Mg1-N2 00 , 133.63(9); N1-Mg1-C20, 115.57 (14); N2 00 -Mg1-C20, 110.28 (14)], and the inner n-butyl appendages point alternately above and below the ring plane, in a similar fashion to that observed in the tetrameric polymorph 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it should be noted that some authors propose an 1,4‐3,4 isomerization to explain the regioselectivity changes observed in the course of an alkyl lithium mediated anionic polymerization of diene conducted in the presence of magnesium dialkyls 41, 42…”
Section: Discussionmentioning
confidence: 99%